Transformation of Islamic Economics in the Society 5.0 Era: An Ethical and Innovation Perspective - Zubairi, Ach.; Huda, Nurul (Journal of Economics and Social Sciences (JESS), 2025)
The rapid development of technology has ushered the world into the era of Society 5.0 a society that emphasizes the integration of technology and humanity. In this context, Islamic economics faces both new challenges and opportunities to transform toward a more adaptive, inclusive, and sustainable system. This study aims to analyze how Islamic economics can adapt in the Society 5.0 era through the synergy between Islamic ethics and technological innovation. The research employs a descriptive qualitative approach based on a literature review of various national and international scientific journals published in the last three years (2022–2025). The findings reveal that the transformation of Islamic economics in the Society 5.0 era is not only characterized by the adoption of digital technologies such as Islamic fintech, halal blockchain, and electronic waqf platforms but also by the application of Islamic ethical values in the innovation process. The principles of maqāṣid al-syarī‘ah particularly the protection of wealth (ḥifẓ al-māl), life (ḥifẓ al-nafs), and religion (ḥifẓ al-dīn) play a vital role in ensuring that every innovation remains aligned with the values of justice, transparency, and public benefit (maṣlaḥah). Furthermore, this study emphasizes that the success of Islamic economic transformation in the Society 5.0 era depends on three key pillars: (1) strengthening the community’s digital literacy and capacity, (2) developing innovations grounded in ethical and just Islamic values, and (3) fostering cross-sector collaboration among the government, academia, and the halal industry. Hence, the synergy between ethics and innovation becomes the cornerstone for realizing an Islamic economy that is not only globally competitive but also contributes to human welfare and global sustainability.